NEWBORNS HEARING SCREENING WITH OTOACOUSTIC EMISSIONS AND AUDITORY BRAINSTEM RESPONSE - Hamam, Kusumagani; Purnami, Nyilo (Universitas Airlangga, 2020)
Hearing loss in newborns is a serious matter, if it is not quickly diagnosed and starts early intervention, a child will experience social, speech, language, cognitive, and academic impairments. There is a method of hearing screening in newborns, which is divided into two types, universal newborn hearing screening, and targeted newborn screening. Both of these methods use OAEs and ABR as objective examination tools. The hearing screening method varies in each country, this difference is based on the test equipment used, age, frequency, professionals involved in screening, referral procedures, funding, and coverage areas. Indonesia uses two stages of screening, while Italy, America, Nigeria, France, India, and Poland use two to five stages of screening. Hearing screening of newborns using OAEs and ABR has a sensitivity of 100% and specificity of 99,3%.